Inhibitory Effect of Protease Inhibitors on Larval Midgut Protease Activities and the Performance of Plutella xylostella (Lepidoptera: Plutellidae) - Zhao, Aiping; Li, Yin; Leng, Chunmeng; Wang, Ping; Li, Yiping (Frontiers in Physiology, 2019)
Plutella xylostella is a pest of cruciferous plants. To understand the relationship between protease inhibitors, protease activities and the growth and development of this insect pest, the activities of midgut proteases of P. xylostella larvae was determined in this study. Protease samples were extracted from the midgut of P. xylostella larvae, and midgut protease activities were determined using enzyme specific substrates. The results showed that CaCl2 inhibited trypsin, EDTA inhibited 4 proteases, and EGTA activated only high-alkaline trypsin. Among the common protease inhibitors, PMSF, TLCK, TPCL, STI (soybean trypsin inhibitor), PMSF had no effect on chymotrypsin but inhibited the other three proteases; TLCK inhibited the first two proteases, while TPCL only activated high-alkaline trypsin. STI had an inhibitory effect on all proteases. These results showed that protease inhibitors can to a certain extent inhibit protease activities in the larval midgut of P. xylostella and that STI can be potentially used toward effective pest control. The performance of P. xylostella was delayed by different inhibitors. These effects were also related to the concentration of the inhibitor. A higher STI concentration had a larger period and lower parameter in this study compared with the CK. The findings of this study may provide new ideas for using protease inhibitors to control pests effectively.